Pengaruh Penatausahaan Aset dan Pemanfaatan Teknologi Informasi Terhadap Ketepatan Waktu Pelaporan Keuangan: Studi Kabupaten Barito Utara - Damanik, Eko Bastian; Hayat, Atma; Sayudi, Akhmad (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2022)
This study aims to determine the effect of human resource competence, leadership commitment, administration of fixed assets and the use of information technology on the timeliness of SOPD financial report submission. Respondents used in this study are SOPD leaders and employees who work in financial management. Data were collected by distributing questionnaires to 112 people, but only 90 questionnaires were returned and could be processed. The sampling technique uses the pusposive sampling method. Data analysis using logistic regression with SPSS version 23. The results of this study indicate that the variable administration of fixed assets and the use of information technology affect the timeliness of SOPD financial statements submission while the variables of human resource competency and leadership commitment do not affect the timeliness of SOPD financial report submission.